(untitled) (Papeles, 2020)
This research, developed at the Master in Education of the Antonio Nariño University (UAN), in Bogotá-Colombia, developed a strategy that mediated in the development of communicative reading and writing skills in the students of the Liceo Femenino Mercedes Nariño IED (LFMN-IED), a public school. The research sought to expose the process that students developed with the communication skills of reading and writing in the dynamics of the school radio station; in addition, it sought to establish, through an evaluative instrument, the initial and achieved skills reading and writing at the semantic, syntactic and pragmatic levels. The school radio station was thought as a space outside the classrooms and regular academic processes, which would boost learning and strengthen the reading and writing skills of the students. A Moodle course was designed, with the “pretext” of working in the processes of the school radio station, developing and strengthening the reading and writing skills of the students who participated in the project, while the radio station was working at school.